WEB-BASED SALES INFORMATION SYSTEM AT CAKI CAKE KARAWANG RESTAURANT - Deni Gunawan; Dwi Puji Hastuti; Ria Andriani; Susafa’ati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
The developments in information and communication technology now is rapidly, particularly in the technology website that can be used on mobile. This technology is not only used by private businesses but the businesses use this technology too, one example is a place of business or a restaurant. The restaurant business person should have a strategy different from other businesses, so it can always be remembered by visitors of the restaurant. For a restaurant businesses can use technology which can help speed up the process of performance, and provide a difference that can attract the attention of visitors. Generally, the restaurant is a form of business that provides a variety of foods and beverages. Every restaurant must serve many orders, if applying the manual booking process will have an impact on the accumulation of orders that are not structured notes, mistakes in writing the order on the name of the menu or the amount of the order. Therefore, by applying the technology developed at this time into the restaurant booking system is expected to control the activities of the booking process to minimize errors. Methods undertaken to produce information with a waterfall model, namely requirements analysis software which then design programs that translate into code generation with PHP web script, JavaScript, JQuery, CSS and framework bootstrap then conducted testing programme and support software are maintenance programs. With the digitalization process can reduce errors presentation sequence order and able to provide information regarding the status of orders.